Improved feed production and utilisation to address year-round feeding systems: guidelines - Devendra, C.; Pezo, Danilo A. (International Livestock Research Institute, 2000)
This paper gives ideas and suggestions to initiate research to address year-round feeding systems, which is one of the major objectives of the Crop-Animal Systems Research Network (CASREN) Project. These ideas and suggestions are discussed in this paper and these are 1) participatory approaches to understand 2) quantitative and qualitative issues in feed availability and use throughout the year 3) adequacy and deficits (availability of nutrients vs. requirements by species 4) intake and grazing studies (on-station) 5) feed production opportunities (examples), and 6) definition of strategies. Methods for estimating the availability of feeds; crop residues, agro-industrial by-products and non-conventional feed resources; and estimation of intake of forages are presented as appendices.